Some Considerations for the Organization of Health Services Emergency and Disaster - Morales, Nelson (2001)
The huge increase in the incidence and severity of injuries that motivate emergency medical care, high costs and disabling consequences they entail, has driven the evolution of infrastructure, management, human resources and materials for hospital emergency services Latin America and the Caribbean. In the big cities of the region significant efforts to implement Systems Services Emergency Medical Care to ensure integrated operation of central control with hospital networks, pre-hospital services and community services are recorded.